2001
DOI: 10.1111/j.1469-445x.2001.tb00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial pressure gradients around joints; location of chief resistance to fluid drainage from the rabbit knee

Abstract: The hypothesis has been advanced that synovium offers the main resistance to fluid escape from joints, even though it is under 20 pm thick. To test this, fluid was infused into the knee joint cavity of anaesthetised rabbits to set up a pressure gradient, then the profde of periarticular interstitial fluid pressure (Pif) was measured by advancing a micropipette, connected to a servo-null pressure recorder, in steps through a periarticular tissue 'window' until the joint cavity was entered. With intra-articular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…2001) was applied over the P j range used to evaluate synovial resistance, namely 2–8 cmH 2 O. Scott et al. (2001) reported that the change in pressure with distance, d P if /dΔ x , was 23.5‐fold greater in the synovium than in the subsynovium, which strongly supports the view that the synovium has a much greater resistivity than the subsynovium.…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…2001) was applied over the P j range used to evaluate synovial resistance, namely 2–8 cmH 2 O. Scott et al. (2001) reported that the change in pressure with distance, d P if /dΔ x , was 23.5‐fold greater in the synovium than in the subsynovium, which strongly supports the view that the synovium has a much greater resistivity than the subsynovium.…”
mentioning
confidence: 76%
“…In the last three groups P j was raised and held constant by a continuous infusion of saline into the joint cavity at a rate that matched fluid drainage across the lining down the measured pressure gradient. Gradients at 15 cmH 2 O are a subset of results reported by Scott et al. (2001).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations